2004
DOI: 10.7202/009109ar
|View full text |Cite
|
Sign up to set email alerts
|

Aridity on the Canadian Plains

Abstract: The Prairie Ecozone is the only major region of Canada where drought is a landscape hazard; aridity is linked to soil erosion. Management of prairie ecosystems and soil landscapes therefore requires an understanding of past and future trends and variability in regional aridity. We used instrumental and paleoclimatic records to define a regional baseline for prairie aridity, to evaluate the utility of modern climate normals (i.e. 1961-1990) as a benchmark for future climatic change, and to provide a historical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 30 publications
2
45
0
Order By: Relevance
“…Within the centennial/ decadal climate variability, climate remains under a very dry regime for long periods (e.g. Sauchyn et al 2002Sauchyn et al , 2003Laird et al 2003;Schindler & Donahue 2006). Under such conditions, it is logical to think that persistent blocking highs are the usual climate pattern over the area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the centennial/ decadal climate variability, climate remains under a very dry regime for long periods (e.g. Sauchyn et al 2002Sauchyn et al , 2003Laird et al 2003;Schindler & Donahue 2006). Under such conditions, it is logical to think that persistent blocking highs are the usual climate pattern over the area.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in several studies using tree rings and lake sediments, Sauchyn et al (2002) found that the climate of the twentieth century in the Canadian Plains was anomalous in terms of drought, as proxy data recorded an abrupt amelioration of climatic conditions near the start of the instrumental record period. While drought was frequent in the twentieth century, it tended to be of shorter duration than during past centuries.…”
Section: Climate and Wildfires In North America M Macias Fauria And Ementioning
confidence: 99%
“…These variations are attested by the instrumental records beginning in the late nineteenth century (Bonsal and Regier, 2007), by proxy data such as paleolimnological studies and tree ring analyses (Sauchyn et al, 2002;Laird et al, 2003;St. George and Sauchyn, 2006) and by historical sources (Rannie, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…We applied this factor to the CRCM data and generated a separate set of climate inputs with this reduced precipitation applied to all of the years in the 2080-2089 period. While this is clearly an extreme drought event, recent paleoclimate research has shown that such decade-scale droughts have occurred in Saskatchewan in the past (Sauchyn et al 2004).…”
Section: Forest Productivitymentioning
confidence: 99%